Pathogenicity of highly pathogenic avian influenza viruses of H5N1 subtype isolated in Thailand for different poultry species - Saito, Takehiko; Watanabe, Chiaki; Takemae, Nobuhiro; Chaisingh, Arunee; Uchida, Yuko; Buranathai, Chantanee; Suzuki, Hirofumi; Okamatsu, Masatoshi; Imada, Tadao; Parchariyanon, Sujira; Traiwanatam, Nimit; Yamaguchi, Shigeo (Veterinary Microbiology, 2009)
Highly pathogenic avian influenza (HPAI) viruses of the H5N1 subtype have caused several rounds of outbreaks in Thailand. In this study, we used 3 HPAI viruses isolated in Thailand in January 2004 from chicken, quail, and duck for genetic and pathogenetic studies. Sequence analysis of the entire genomes of these isolates revealed that they were genetically similar to each other. Chickens, quails, domestic ducks, and cross-bred ducks were inoculated with these isolates to evaluate their pathogenicity to different host species. A/chicken/Yamaguchi/7/04 (H5N1), an HPAI virus isolated in Japan, was also used in the chicken and quail studies for comparison. All four isolates were shown to be highly pathogenic to chickens and quails, with 100% mortality by 10 6 EID 50 inoculants of the viruses. They caused sudden death in chickens and quails within 2–4 days after inoculation. The mean death times (MDT) of quails infected with the Thai isolates were shorter than those of chickens infected with the same isolates. Mortality against domestic and cross-bred ducks ranged from 50 to 75% by intranasal inoculation with the 10 6 EID 50 viruses. Neurological symptoms were observed in most of the inoculated domestic ducks and appeared less severe in the cross-bred ducks. The MDTs of the ducks infected with the Thai isolates were 4.8–6 days post-inoculation. Most of the surviving ducks infected with the Thai isolates had sero-converted until 14 dpi. Our study illustrated the pathobiology of the Thai isolates against different poultry species and would provide useful information for improving control strategies against HPAI.